NEW DESCRIPTION OF THE ROTALIPORID SPECIES BROTZENI AND GLOBOTRUNCANOIDES SIGAL, 1948 BASED ON RE-EXAMINATION OF TYPE MATERIAL - MICHELE CARON; ISABELLA PREMOLI SILVA (Rivista Italiana di Paleontologia e Stratigrafia, 2007)
This short notes deals with the re-description and re-illustration of the holotypes of Thalmanninella brotzeni Sigal, 1948 and Rotalipora globotruncanoides Sigal, 1948, from Sidi Aissa, Algeria, middle Cenomanian. Both species are attributed to the genus Thalmanninella.